2014
DOI: 10.5603/imh.2014.0013
|View full text |Cite
|
Sign up to set email alerts
|

Vibration on board and health effects

Abstract: (Int Marit Health 2014; 64, 2: 58-60)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Indeed, animal studies found that exposure to continuous quantitative vibration diminished the proteoglycan content in the nucleus pulposus disrupting the integrity of the matrix and increasing the instability of the intervertebral disc [30]. The results of our study support the possibility of an association with occupational driving and of course workers in the agricultural/fishing industries may also be exposed to whole-body vibration in tractors or boats [31, 32].…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, animal studies found that exposure to continuous quantitative vibration diminished the proteoglycan content in the nucleus pulposus disrupting the integrity of the matrix and increasing the instability of the intervertebral disc [30]. The results of our study support the possibility of an association with occupational driving and of course workers in the agricultural/fishing industries may also be exposed to whole-body vibration in tractors or boats [31, 32].…”
Section: Discussionsupporting
confidence: 66%
“…Today, there is a lack of knowledge regarding levels of WBV and health effects in the merchant fleet (Jensen and Jepsen 2014). In our study, pain or discomfort in the back, hips and knees as well as sleep disturbances and unusual tiredness were more commonly reported if exposed to whole-body vibrations (WBV).…”
Section: Discussionmentioning
confidence: 99%
“…seasickness) [13,14] or even result in health impairment (e.g. lower back pain, abnormalities in intervertebral discs) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%